Infrastructure Development in Malaysia: How Planning System Regulates Local Infrastructure Provision? - Salleh, Dani; Junaiadi, Noni Harianti (2023)
In Malaysia, due to limited financial resources, local governments can no longer act as the sole providers of local infrastructure. Therefore, the study explores the shift in Malaysia's infrastructure provision, transitioning from public sector dominance to increased private sector involvement. However, as urban growth surged, and with financial constraints evident, there emerged a pressing need for alternative strategies. Currently, infrastructure provision is a joint responsibility between public and private sectors. A consistent challenge has been the non-standardized conditions imposed by local authorities. The findings of the study proposes enhancing the current system by integrating efficient negotiation framework into the planning approval process and diversifying infrastructure delivery methods. Infrastructure delivery methods, such as BOT, PPP, and PFI, are suggested to diversify the approach. The Integrated Planning Approval System could lead to a more equitable infrastructure cost distribution. The role of the private sector in enhancing efficiency in local infrastructure development is becoming more pronounced, offering potential enhancements to community living standards. The paper warns of the current model's shortcomings, which may deplete resources for other vital community needs. Key proposed solutions include leveraging the current planning framework to recuperate costs from beneficiaries, focusing on privatization schemes, and emphasizing policies ensuring efficiency and environmental considerations in infrastructure projects. The ultimate objective is to establish a model balancing efficiency, acceptability, and feasibility in local infrastructure provision. The discussion concludes by suggesting local authorities consider privatization schemes for financial relief and efficiency, emphasizing pricing policies that cover full costs and account for environmental impacts.